Five-Level Multiple-Pole Mutlilevel Diode-Clamped Inverter Scheme for Reactive Power Compensation - Raj, Pinkymol Harikrishna (2016)
This paper proposes a space vector modulation based dc-link capacitor voltage balancing technique for a five-level multiple-pole multilevel diode-clamped (M2DCI) inverter. The new five-level inverter contains lesser number of clamping diodes compared to the conventional five-level diode-clamped inverter (DCI) topology and does not require any extra balancing circuits to maintain balanced voltages across the four dc-link capacitors. The effect of load power factor and modulation indices on voltage balancing strategy has been studied, and the stability region for five-level M2DCI is determined based on investigation done in the Matlab/Simulink?? and PSIM environment during balanced, unbalanced and distorted load conditions. The proposed reduced device topology with SVM technique, which self balances the dc-link capacitors can be very attractive for reactive power control in a grid connected environment.